An evaluation of Universiti Teknologi MARA tobacco free policy initiative on acceptance, awareness, and enforcement / Diyana Shereen Anwar - Anwar, Diyana Shereen (2020)
Introduction: Universiti Teknologi MARA launched the Tobacco Free Campus Initiative in January 2016 in its UiTM Sungai Buloh Campus. Despite the policy being in place for 4 years, no study has been done to evaluate the acceptance, process, and enforcement of the policy. Objectives: To assess the policy in its adherence to the gold standard of policy making, to evaluate the TFI policy in terms of acceptance, awareness, and enforcement, and to evaluate the implementation of the TFI policy in terms of communication and dissemination, enforcement, compliance, and programmes offered, and to evaluate the barriers and facilitators in the enforcement of TFI policy. Methods: The American College Health Association (ACHA)’s tobacco free campus policy guidelines were used as a checklist to see the adherence of UiTM TFI policy to the gold standard of tobacco policy. A cross-sectional survey was administered to students, staff, patients, and vendors to assess their acceptance, awareness, and perception on policy enforcement. Checklists were used to evaluate the communication and dissemination of policy, enforcement, compliance and programs offered. Lastly, a focus group discussion was conducted to evaluate the barriers and facilitators in the enforcement of TFI policy. Results: UiTM TFI policy adhered to the gold standard of tobacco policy by 95%. More than half of the respondents reported acceptance towards the UiTM tobacco free policy. Similarly, a majority of respondents agreed on the policy being enforced in the campus. In contrast, findings in terms of awareness were low where only 23.7% reported of having awareness of the policy. Qualitative findings also indicate low compliance of the policy. Main barrier identified was lack of support, and the main facilitating factor identified were TFI buddies. Conclusion: Overall awareness of the TFI policy is low, acceptance of the policy is good amongst staff and students but low amongst patients. Compliance and enforcement of the policy is also weak. Barriers and facilitating factors identified should be examined and addressed by the stakeholders to allow for policy improvement.